As experiências como revendedoras de cosméticos da empresa Avon na cidade de João Pessoa - Felix, Maria da Conceição Silva (2020)
Personal selling, door-to-door selling and home selling are nomenclatures that also define the direct selling system. The sector has been growing for the last twenty years as a large labor and consumer market. According to data provided by the Brazilian Direct Selling Association, in the last decade alone the sector has quadrupled in size in Brazil and has already grown to become the third largest in the world market. The aim of this research is to unveil the universe of women resellers of cosmetic products of the Avon company, in order to perceive this activity from the point of view of its main protagonists. The methodological and theoretical basis is supported by Oral History, having an interview as the data collection instrument. Starting from the qualitative approach, we included in the database qualitative data and bibliographic information obtained from documentary sources. The data was obtained through the testimonials of the resellers, the written information present in labor lawsuits, newspapers, magazines, the Avon catalogs, as well as surveys conducted by IBGE, IPEA, ABEVD, ABIHPEC and Avon itself. The guiding hypothesis of the research was that the growth of the cosmetics industry is linked to the spreading of beauty standards, influenced by vanity, manipulated by consumption, constantly creating new needs in individuals. From the analysis, it was observed that the results show that informal labour, characterized by the type of direct selling through autonomous dealers, indicates that there is a satisfaction in developing this activity, despite the evident precariousness of work, which seems contradictory